2007
DOI: 10.1038/sj.bjc.6603633
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness, safety and acceptability of ‘see and treat’ with cryotherapy by nurses in a cervical screening study in India

Abstract: We evaluated a 'see and treat' procedure involving screening, colposcopy, biopsy and cryotherapy by trained nurses in one-visit in field clinics in a cervical screening study in South India for its acceptability, safety and effectiveness in curing cervical intraepithelial neoplasia (CIN). Women positive on visual inspection with acetic acid (VIA) were advised colposcopy, directed biopsies and cryotherapy if they had colposcopic impression of CIN in one visit by nurses in field clinics supervised by a doctor. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
148
4
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(167 citation statements)
references
References 7 publications
(8 reference statements)
10
148
4
5
Order By: Relevance
“…23 Similarly, most ACCP studies have shown extremely low rates of serious adverse events requiring hospitalization, with the most common side effects being fever, pain, watery discharge, bleeding and cramping. 20,25,26 Data from a study conducted by Denny et al 20 in South Africa further confirm the safety of this therapy. Among the almost 950 women who underwent cryotherapy after an initial positive HPV DNA or VIA test, only one experienced a serious adverse event (a woman who refused hospitalization for cervical bleeding).…”
Section: Alternative Cervical Cancer Screening Approaches In Low-resomentioning
confidence: 64%
See 1 more Smart Citation
“…23 Similarly, most ACCP studies have shown extremely low rates of serious adverse events requiring hospitalization, with the most common side effects being fever, pain, watery discharge, bleeding and cramping. 20,25,26 Data from a study conducted by Denny et al 20 in South Africa further confirm the safety of this therapy. Among the almost 950 women who underwent cryotherapy after an initial positive HPV DNA or VIA test, only one experienced a serious adverse event (a woman who refused hospitalization for cervical bleeding).…”
Section: Alternative Cervical Cancer Screening Approaches In Low-resomentioning
confidence: 64%
“…24 In this study, the therapy was provided by general physicians, but midwives or other midlevel providers have performed the procedure in other settings with similar results. For example, in Dindigul district in India, Sankaranarayanan et al 25 found an overall cure rate of 81% among women with CIN 1 and 71% among women with CIN 2-3 when cryotherapy was provided by nurses in field clinics.…”
Section: Alternative Cervical Cancer Screening Approaches In Low-resomentioning
confidence: 99%
“…46,47 In a study of nearly 80,000 women in India aged 30-59 screened with VIA, there was a 25% reduction in cervical cancer incidence and 35% reduction in cancer deaths, as compared to a control group that was not screened. Benefits were most marked for women in their 30s.…”
Section: Making Screening and Pre-cancer Treatment Accessiblementioning
confidence: 99%
“…R Sankaranarayanan and colleagues from India, concluded that 'see and treat' with cryotherapy by nurses under medical supervision is acceptable, safe and effective method for cervical cancer prevention in low-resource settings. 5 Mariategui J and co-workers have stated that CO2-cryotherapy may be less effective than N2O-cryotherapy for complete destruction of cervical precancerous lesions. 12 In present study, the age of the patients varied between twenty to forty years.…”
mentioning
confidence: 99%